Effectiveness of Card Sort Learning Method to Improve Students' Cognitive in Kemuhammadiyahan Learning - Tamami, Fauziyah Qurrota Ayun; Shohib, Muhammad Wildan; Rahmawati, Siti (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The study aims to investigate the effectiveness of the card sort learning method in improving students’ cognitive students in Kemuhammadiyahan learning at Muhammadiyah 2 Surakarta High School, Indonesia. Methodology: This research is quantitative by the environment, and the data was gathered through the use of questionnaires, observation, and documentation. Descriptive analysis and basic linear regression tests were employed to analyze the data. Results: The outcome of this investigation proves that the level of student perspective towards the card sort learning method and the learning achievement of students in the Muhammadiyah subject are in a positive category. The findings of the average mean score demonstrate the Muhammadiyah subject perceived level at 45.41% and the card sort method perceived level at 43.2%. The partial t-test (t = 8.276, p = 0.000) shows that the total cart sort learning method is linked to the overall learning outcomes of Muhammadiyah studies. The results of the significant prediction equation are built as Total Kemuhammadiyahan Learning = 0.933 + 0.129 (Total Card Sort Method). It can be possible to deduce that Ho is rejected and Ha is somewhat accepted, and therefore the card sort method significantly improves and predicts students' cognitive achievement in Muhammadiyah studies. Applications/Originality/Value: According to the study’s result, a card-sort learning method can be used effectively to improve students' cognitive aspects while learning Muhammadiyah studies. This study makes a significant contribution to the understanding of the card sort learning method as an effective instrument to develop the student’s cognitive abilities in learning Muhammadiyah studies.